Towards Composable Location Models in Ubiquitous Computing Applications - Robles Luna, Esteban (2012)
The state of the art in location models falls short to adapt to new requirements such as composition and integration of maps. Composing and integrating maps are typical operations we want to apply when we deal with ubiquitous computing applications because they evolve permanently (i.e. to add location information of new cities, buildings, means of transport, etc). We propose a novel approach that by abstracting some concepts such as located objects and locations, can result in more flexible models, therefore allowing dynamic composition and integration of maps. With this approach, it is also possible to combine different location representations, making applications easier to extend.